2004
DOI: 10.1007/s00384-004-0601-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the proto-oncogene c-KIT in normal and tumor tissues from colorectal carcinoma patients

Abstract: Background and aims: The proto-oncogene c-KIT encodes a tyrosine kinase receptor essential during embryonic development and postnatal life. Although deregulated expression of c-KIT has been reported, its role in colorectal carcinoma remains controversial: some authors have described a correlation between c-KIT expression and colorectal cancer (CRC), while others have failed to detect the receptor in the majority of neoplasia examined. To address this question, we designed a prospective study to analyze the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 27 publications
(34 reference statements)
4
42
0
2
Order By: Relevance
“…In another study, faint cytoplasmic KIT positivity was found in 4.8% of CRC cases (8). More recently, Sammarco et al detected KIT-positive staining in the epithelium of the neoplastic colon in 25% of patients examined (10). In a previous preliminary analysis conducted on a small number of patients, we reported KIT immunoreactivity in several malignant mucosa specimens compared to normal counterparts (38).…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…In another study, faint cytoplasmic KIT positivity was found in 4.8% of CRC cases (8). More recently, Sammarco et al detected KIT-positive staining in the epithelium of the neoplastic colon in 25% of patients examined (10). In a previous preliminary analysis conducted on a small number of patients, we reported KIT immunoreactivity in several malignant mucosa specimens compared to normal counterparts (38).…”
Section: Discussionsupporting
confidence: 48%
“…The lesson learned from clinical trials of imatinib in GIST is that the mutational status of c-kit is required to achieve a successful response and improve survival (62). The presence of a truncated c-kit form with potentially strong activation capacity has been reported in some colon carcinoma cell lines (54,63) and, at the moment, in a single CRC patient (10). However, since we detected SCF in the majority of KIT-positive CRCs, it is conceivable that, in this tumor, activation of the receptor may be supported by this autocrine circuit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant expression of c-Kit and/ or stem cell factor has been reported in gastrointestinal stromal tumors and colon cancer cell lines [18][19][20] ; however, data regarding c-Kit expression in CRC remain scarce. 21 Cyclooxygenase-2 (COX-2) is an inducible enzyme that regulates prostaglandin synthesis. It is overexpressed at sites of inflammation and in several epithelial cancers, in which it is involved in apoptosis resistance, angiogenesis, and tumor cell invasiveness.…”
mentioning
confidence: 99%
“…It is overexpressed at sites of inflammation and in several epithelial cancers, in which it is involved in apoptosis resistance, angiogenesis, and tumor cell invasiveness. 21 Forced COX-2 expression suppresses apoptosis by modulating the level of death receptor 5, an effect that can be reversed by COX-2 inhibitors. 21,22 Several studies have reported COX-2 overexpression in human colon cancers and adenomas, thus making COX-2 a potential target for chemoprevention trials.…”
mentioning
confidence: 99%